Factors associated with tuberculosis disease among children who are household contacts of tuberculosis cases in an urban setting in Malaysia - Azit, Noor Atika (BMC Public Health, 2019)
BACKGROUND: With the rise in prevalence of childhood tuberculosis (TB) globally, contact tracing should be a powerful strategy for early diagnosis and management, especially in children who are household contacts of active TB cases. Here, we aimed to determine the prevalence and factors associated with TB disease in children who are household contacts of TB cases. METHODS: We used a cross-sectional study with data from the Malaysian TB Information System (TBIS) recorded from 1 January 2014 to 31 December 2017. All children aged 0–14 years who were registered in the TBIS with at least one household contact of TB cases were included in the study. Multiple logistic regression analysis was performed to calculate the adjusted odds ratio (adj. OR) and for adjusting the confounding factors. RESULTS: A total of 2793 children were included in the study. The prevalence of active TB was 1.5% (95% confidence interval [CI]: 1.31, 1.77%). Children aged < 5 years [adj. OR 9.48 (95% CI: 3.41, 26.36) p < 0.001] with positive tuberculin skin test [adj. OR 395.73 (95% CI: 134.17, 1167.13), p < 0.001] and investigation period of > 6 weeks [adj. OR 7.48 (95% CI: 2.88, 19.43), p < 0.001] had significantly higher odds for TB disease. CONCLUSIONS: The prevalence of TB disease in children who were household contacts of TB cases is relatively low. However, contact tracing programmes should not only focus on children aged < 5 years and with positive tuberculin skin test results, but also be empowered to reduce the investigation period.